THE EFFECT OF LIQUIDITY, LEVERAGE, AND BUSINESS RISK ON FINANCIAL PERFORMANCE IN THE CONSUMER CYCLICALS SECTOR - Anak Agung Sagung Intan Sita Parameswari; I Gst Ayu Eka Damayanthi (Adisam Publisher, 2025)
Financial performance is an essential indicator for assessing the effectiveness of a company’s asset management. The consumer cyclicals sector listed on the Indonesia Stock Exchange (IDX) experienced significant fluctuations in financial performance during 2021–2023, highlighting the need to examine its determining factors. This study aims to obtain empirical evidence regarding the influence of liquidity, leverage, and business risk on financial performance. A quantitative approach was employed using secondary data derived from the financial statements of consumer cyclicals companies listed on the IDX. The research sample was selected using purposive sampling, resulting in 46 companies and 81 observations. Data were analyzed using multiple linear regression with SPSS. The findings indicate that liquidity has no effect on financial performance, leverage has no effect on financial performance, while business risk has a positive effect on financial performance. These results suggest that financial performance in this sector is more strongly determined by business risk management than by liquidity or leverage.